2022
DOI: 10.1111/apce.12389
|View full text |Cite
|
Sign up to set email alerts
|

How much of the world economy is state‐owned? Analysis based on the 2005–20 Fortune Global 500 lists

Abstract: This paper analyzes the share of state‐owned enterprises on the Fortune Global 500 lists from 2005 to 2020. The purpose is to answer two research questions—what is the share of SOEs among the world's largest companies, and is this share increasing over the years? Regarding studies of large sets of companies, the novelty of this article is the method in which SOEs were identified—based on the criterion of actual corporate control of the state and not the threshold of state ownership. The results show that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The IG producer maximizes the operating profit as in ( 10) and the price for IG i is (11). As IGs are bought to the same extent x i = x, we can present (28) as…”
Section: Final Goods and Intermediate Goods Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IG producer maximizes the operating profit as in ( 10) and the price for IG i is (11). As IGs are bought to the same extent x i = x, we can present (28) as…”
Section: Final Goods and Intermediate Goods Productionmentioning
confidence: 99%
“…Szarzec et al (2021) showed that SOEs had at least a 20% share in the group of large enterprises in 19 out of 30 European countries in 2007-16. Kwiatkowski et al (2022) found 141 SOEs among the 500 largest enterprises worldwide in 2020. However, SOEs are most often analyzed at the microeconomic level and there is little research into their impact on economic growth, particularly from the theoretical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The recent findings of the IMF (2020) show that the share of SOEs among the world's 2000 largest firms doubled to 20% over the last two decades, driven by SOEs in emerging markets—their assets being worth US$45 trillion, equivalent to half of the global GDP. As for the Fortune Global 500 list, the shares of SOEs in the group of the world's largest companies have increased from 64 SOEs in 2005 to 141 SOEs in 2020 (Kwiatkowski et al, 2023). In 19 out of 30 European countries during the period 2007 to 2016, SOEs held a minimum share of 20% in the majority of large enterprises (Szarzec et al, 2021).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%